Progress in implementation of WHO FCTC Article 14 and its guidelines: a survey of tobacco dependence treatment provision in 142 countries - Nilan, Kapka; Raw, Martin; McKeever, Tricia M.; Murray, Rachael L.; McNeill, Ann (Wiley, 2017)
Aims To 1) estimate the number of Parties to the Framework Convention on Tobacco Control (FCTC) providing tobacco dependence treatment in accordance with the recommendations of Article 14 and its guidelines; 2) assess association between provision and countries’ income level; and 3) assess progress over time. Design Cross sectional study. Setting Online survey from December 2014 to July 2015. Participants Contacts in 172 countries were surveyed, representing 169 of the 180 FCTC Parties at the time of the survey. Measurements A 26 item questionnaire based on the Article 14 recommendations including tobacco treatment infrastructure and cessation support systems. Progress over time was assessed for those countries that also participated in our 2012 survey and did not change country income level classification. Findings We received responses from contacts in 142 countries, an 83% response rate. Overall, 54% of respondents reported their country had an officially identified person responsible for tobacco dependence treatment, 32% an official national treatment strategy, 40% official national treatment guidelines, 25% a clearly identified budget for treatment, 17% text messaging, 23% free national quitlines, and 26% specialised treatment services. Most measures were positively and significantly associated with countries’ income level (p=0.001). Measures not significantly associated with income level included mandatory recording of tobacco use (30% of countries), offering help to healthcare workers (HCW) to stop using tobacco (44%), brief advice integrated into existing services (44%), and training HCW to give brief advice (81%). Reporting having an officially identified person responsible for tobacco cessation was the only measure with a statistically significant improvement over time (p=0.0351). Conclusion Fewer than half of countries that are Parties to the Framework Convention on Tobacco Control have implemented the recommendations of Article 14 and its guidelines, and for most measures, provision was greater the higher the country’s income. There was little improvement in treatment provision between 2012 and 2015 in all countries.